IMPLEMENTATION OF A DEEP LEARNING APPROACH ASSISTED BY THE POLITE PALS MEDIA IN COURTEOUS SPEAKING INSTRUCTION - Radita Hasanah; Ahmad Rijal Hakim Fathulloh; Bernadus Wahyudi Joko Santoso (Program Studi PGSD Universitas Flores, 2026)
Understanding speech politeness is essential for students to apply it in daily communication. However, students’ level of understanding remains low, indicating the need for innovative instructional approaches. This study aims to examine (1) differences in students’ understanding of speech politeness between those taught using a Deep Learning approach assisted by E-Comic media and those in a control group, and (2) the effectiveness of the Deep Learning approach in improving students’ understanding of polite speech. This study employed a quasi-experimental method with a nonequivalent control group design, involving first-grade students (Classes IA and IB) from an elementary school in Semarang City. Data were analyzed using tests of normality and homogeneity, followed by hypothesis testing. The Polite Pals e-comic integrates principles of mindful, meaningful, and joyful learning. The t-test results yielded a p-value of 0.006 (< 0.05), indicating that H? is rejected and H? is accepted. The N-gain score for the experimental class was 0.7345, while the control class obtained 0.6095. These findings suggest that the Deep Learning approach assisted by the Polite Pals e-comic is effective in enhancing students’ understanding of polite speech.